Fokalisasi Perundungan dalam Film From the Ashes Karya Khalid Fahad (Kajian Naratologi Gerard Gennete): FOCALIZATION OF BULLYING - Putri Salma Febriana; Rohanda Rohanda (Universitas Muhammadiyah Surabaya, 2026)
This study investigates how focalization techniques are applied in Khalid Fahad's From The Ashes, with reference to the narratological theoretical framework developed by Gérard Genette. The main focus of the research lies on three types of focalization: zero focalization, internal focalization, and external focalization. Through a qualitative-descriptive method, this study identifies and analyzes how the three types of focalization are used in conveying the narrative, shaping the audience's perception, and building social meaning in the storyline. The results show that the film is dominated by a fixed internal focus centered on the main character who is a victim of bullying, thus presenting a subjective and empathetic narrative. In addition, there is also a shift to zero focalization in some scenes that show the objective reality of bullying as a social phenomenon. In other words, From the Ashes not only depicts the personal experiences of the victims, but also highlights the structural and systemic aspects of bullying in a broader social context. This research aims at how focalization strategies can reinforce social criticism and moral messages in cinematic works.